Wall-diaphragm interactions in seismic response of single-story building systems. (15th November 2021) - Fischer, Astrid W.; Schafer, Benjamin W.
Highlights: Wall and diaphragm interactions effect the building period and force demands. Inelasticity in either walls or roof diaphragms can decrease force demands. Wall inelasticity decreases demands more efficiently than diaphragm inelasticity. Ductility demands may be greater than typically with wall-diaphragm interaction. ASCE 7-16 design methods are accurate for predicting rigid diaphragm force demands. Abstract: The objective of this paper is to investigate the seismic time history response of single-story buildings with a wide range of wall and roof diaphragm periods and ductility. Current design specifications, e.g., ASCE 7-16, are transitioning from accounting for inelasticity in only the vertical lateral force resisting systems, i.e., the walls, to including inelasticity in the horizontal lateral force resisting system, i.e., the roof diaphragm. It is not clear if the wall and roof inelasticity can be considered independently, nor if they can utilize their own seismic response modification coefficients. More fundamentally, the basic manner in which stiffness, mass, and ductility of the wall and roof interact is not fully understood. Here, a single-story building is approximated with a reduced order mass-spring model and parameters are varied so that a wide range of wall periods, diaphragm periods, and wall and diaphragm inelasticity are explored. The model is imposed to vibration analyses, elastic time history analyses, and inelastic time history analyses. The results show clear regimes where the wall and diaphragms interact, and those where the response is largely independent. When inelasticity occurs the ductility demands can be significant for the building component, wall or diaphragm, that initiates the yielding, and greater than traditionally expected. The model results are compared to current and proposed provisions for predicting force and ductility demands and conclusions are drawn with respect to the accuracy of available methods.